Study on referral of patients in the Department of Physical Medicine & Rehabilitation in Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i2.3869Journal of Chittagong Medical College Teachers' Association 2008: 19(2):39-42